SALMONELLOSIS OF WATERFOWL - Mussayeva , A.K.; Yegorova, N.N.; Nurpeisova , A.S.; Utegenova , M.E.; Kasenov , M.M. (Eurasian Journal of Applied Biotechnology, 2025)
The article presents the results of studying the biological properties and identification of 19 Salmonella isolates isolated from ducklings. The relevance of these studies is due to the widespread occurrence of Salmonellosis in waterfowl (SWF), regardless of the region or climate conditions. Salmonellosis in waterfowl (ducks, geese) causes significant damage to farms and is the main cause of death among chicks. Young birds are most susceptible from day 1 to day 45 of life. Poultry salmonellosis becomes widespread, accompanied by bacteremia, severe toxicosis, and exhaustion that leads to death. The disease manifests itself as septicemia and diarrhea in young birds, and as latent bacteriosis in adult birds. Birds that have recovered from salmonellosis remain carriers for life and are a source of infection and spread. Sick birds and carriers are a source of human salmonellosis (toxigenic infection). The occurrence, spread, and course of salmonellosis in birds are determined by the epizootic health of the farms and the immunological reactivity of the birds, as poultry is the most dependent on environmental factors. Environmental pollution, water bodies, and feed, prolonged carriage of Salmonella, the circulation of antibiotic-resistant Salmonella populations, the spread of infection by rodents, and the lack of specific disease prevention are all factors that contribute to the spread of infection. The purpose of the research is to make a diagnosis in case of clinical suspicion of an infection of unknown etiology in ducklings, to identify birds that are carriers of Salmonella, and to isolate the pathogen. The object of the study is biological and pathological material from 3 dead and 16 sick ducklings aged 14 days, which were delivered from a farm in the Almaty region. The research used bacteriological, serological, and biochemical methods. The cultural and morphological properties of Salmonella were studied by growing them on meat-peptone broth, meat-peptone agar, and differential-diagnostic media (Endo medium, bismuth sulfite agar). Microscopy was performed on smears prepared from 24-hour agar cultures, which were Gram-stained and prepared using a simple method. The biochemical properties of the isolated cultures were studied by growing them on Giss medium with carbohydrates. The motility of Salmonella was determined by its growth on semi-liquid agar. To detect proteolytic activity, the test cultures were grown on meat-peptone gelatin. The Salmonella cultures isolated from ducklings were differentiated based on their cultural, morphological, tinctorial, biochemical, and antigenic properties, as well as the results of bioassay on laboratory animals. Bacteriological diagnosis of ducklings' salmonellosis based on the results of pathological material examination, as well as feces from sick ducklings, with a mandatory study of the biological properties of isolated Salmonella